Design, fabrication, and demonstration of low-mass, low-power, small-volume, direct detection millimeter-wave radiometers at 92 and 130 GHz - Albers, Darrin, author; Reising, Steven C., advisor; Kummerow, Christian, committee member; Notaros, Branislav, committee member; Kangaslahti, Pekka, committee member (Colorado State University. Libraries, 2012)
Advances in future ocean satellite altimetry missions are needed to meet oceanographic and hydrological objectives. These needs include accurately determining the sea surface height (SSH) on spatial scales of 10 km and larger, as well as monitoring the height of the world's inland bodies of water and the flow rate of rivers. The Surface Water and Ocean Topography (SWOT) mission was recommended by the National Research Council's Earth Science Decadal Survey and selected by the National Aeronautics and Space Administration as an accelerated Tier-2 mission to address these needs. Current surface altimetry missions use nadir pointing 18-37 GHz microwave radiometers to correct for errors in SSH due to wet-tropospheric path delay. Using current antennas at these frequencies, oceanic measurements include significant errors within 50 km of coastlines due to varying emissivity and temperature of land. Higher frequencies (90-170 GHz) can provide proportionally smaller footprints for the same antenna size. In turn, this provides improved retrievals of wet-tropospheric path delay near the coasts. This thesis will focus on the design, fabrication, and testing of two direct detection radiometers with internal calibration at center frequencies of 92 and 130 GHz. Component design, testing and integration of the radiometers using multi-chip modules are discussed. The performance of these radiometers is characterized, including noise figure, internal calibration and long-term stability. These performance parameters, along with their mass, volume, and power consumption, will be used as the basis for the development of future airborne and space-borne millimeter-wave direct detection radiometers with internal calibration.
Keywords: microwave; radiometer